Effectiveness of COVID-19 Vaccine on Augmenting Antibody Level in People in the Special Region of Yogyakarta, Indonesia - Joko Budiyono; Bhisma Murti; Didik Gunawan Tamtomo (Journal of Epidemiology and Public Health, 2024)
Background: Immunity against SARS-CoV-2 is needed to prevent infection so vaccines are indeed humanity's great hope as a weapon to control COVID-19. Seroprevalence data is needed using an antibody test that estimates the percentage of DIY residents who have antibodies against SARS-CoV-2. This study aimed to determine the effectiveness of COVID-19 vaccination on enhancing antibody titers.Subjects and Method: This was a retrospective cohort study conducted in Yogyakarta, Indonesia, from 19 to 30 November 2021. The study population was people aged ≥1 year. A total of 563 study subjects was selected randomly. The dependent variable was the SARS-CoV-2 antibody titer level. The independent variables were COVID-19 vaccination status, gender, age, smoking, outdoor activities, and alcohol consumption. SARS-CoV-2 antibody level was measured using Roche's Elecsys anti-SARS-CoV-2. Other variables were collected using questionnaires. Data were analyzed using a multiple linear regression run on STATA 14.Results: The initial vaccination led to an elevation in -19 antibody titers, but it was statistically non-significant (b= 697.82; 95% CI= -720.90 to 1241.24; p= 0.603). The second vaccination resulted in a notable and statistically significant elevation of COVID-19 antibody titers (b= 1331.38; 95% CI= 802.30 to 1860.46; p <0.001).Conclusion: The second dose of the COVID-19 vaccination demonstrated significant effectiveness in boosting COVID-19 antibody titers. Keywords: COVID-19, vaccination, antibody